Gerald Martin, Gabriel García Márquez. Una vida. Trad. de Eugenia Vásquez Nacarino. Debate, Colombia, 2009; 762 pp. - Díaz Ruíz, Ignacio (El Colegio de México, 2011)
Se reseña el libro:Gabriel García Márquez. Una vida.